Pengaruh Brain-Based Learning Terhadap Kemampuan Berpikir Kritis Ditinjau Dari Self Confidance Pada Pembelajaran Matematika - Lastri Lastri; Iva Sarifah; Indra Jaya (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
This study aims to examine the role of the Brain-Based Learning model and students' self-confidence levels in influencing critical thinking skills in elementary school math lessons. The research uses a quantitative approach with a 2×2 factorial quasi-experimental design. The subjects of the study were fifth-grade students grouped based on the learning model they received as well as based on high and low self-confidence categories. Data were collected through critical thinking skill tests and self-confidence questionnaires, then analyzed using two-way analysis of variance. The research results show that applying Brain-Based Learning has a significant impact on students' critical thinking skills. Students' level of self-confidence also proves to contribute significantly to achieving these skills. Further analysis reveals an interaction between the learning model and self-confidence, indicating that the effectiveness of the learning model differs according to students' self-confidence characteristics. Students with high self-confidence achieve better results when engaging in BBL-based learning, while students with low self-confidence show better outcomes through cooperative learning of the STAD type. These findings suggest that the development of critical thinking skills is influenced by a mix of cognitive and affective factors.